Outcome of Continuous Cerebral and Myocardial Perfusion Under Mild Hypothermia for Aortic Coarctation with Ventricular Septal Defect Repair12. Issue 1 (21st January 2013) - Chen, Huiwen; Zhang, Haibo; Hong, Haifa; Zhu, Zhongqun; Liu, Jinfen
Abstract Background: Controversy still exists on the use of the optimal cardiopulmonary bypass (CPB) management in aortic coarctation (CoA) with ventricular septal defect (VSD) repair. We report the outcome of patients undergoing continuous cerebral and myocardial perfusion (CCMP) under mild hypothermia. Method: This is a retrospective analysis of 60 consecutive patients undergoing anatomic reconstruction of CoA with VSD closure between 1999 and 2011. Single arterial cannula perfusion technique was used in 15 (25%) patients, and a dual arterial cannula perfusion technique was used in 45 (75%) patients. Results: There were no hospital or late mortalities. Average CPB time was 105 ± 28 minutes, aortic clamp 27 ± 7 minutes, and descending aortic cross‐clamp time 24 ± 5 minutes. Average continuous cerebral perfusion flow was 64 ± 8 mL/kg per minute. No patient needed delayed sternal closure. Average duration of ventilation was 38 ± 20 hours, ICU stay 7 ± 3 days, and hospital stay 14 ± 6 days. No patient required revision for bleeding and/or extracorporeal membrane oxygenation support. No neurologic complications were noted. Conclusion: A perfusion strategy using CCMP with mild hypothermia for CoA and VSD repair is feasible and safe.